Intellectual humility and the learning sciences: can self-reports and behavioral measures coexist to understand civic engagement? - Lira, Matthew; McElroy-Heltzel, Stacey (Frontiers in Psychology, 2024)
Recent political events across the globe have illustrated a resurgence in people's intolerance to ideas different from their own. We mobilize the idea of intellectual humility to assess how extant psychological theories account for individual differences in people's tolerance for conflicting ideas. Then, we introduce concepts from the Learning Sciences to determine how alternative methodologies could augment research on intellectual humility and civic engagement. Last, we summarize these analyses by pointing to their relations with three intersecting challenges and solutions regarding studying IH in multiple contexts and with new multiple data sources.